2014
DOI: 10.1371/journal.pone.0093370
|View full text |Cite
|
Sign up to set email alerts
|

Slow Food: Sustained Impact of Harder Foods on the Reduction in Energy Intake over the Course of the Day

Abstract: BackgroundPrevious research has shown that oral processing characteristics like bite size and oral residence duration are related to the satiating efficiency of foods. Oral processing characteristics are influenced by food texture. Very little research has been done on the effect of food texture within solid foods on energy intake.ObjectivesThe first objective was to investigate the effect of hardness of food on energy intake at lunch, and to link this effect to differences in food oral processing characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(169 citation statements)
references
References 39 publications
7
162
0
Order By: Relevance
“…However, the results are in line with several cross-over and mostly laboratory studies have consistently shown that reducing bite sizes or eating rate within individuals decrease food intake (Andrade, Greene, & Melanson, 2008;Bolhuis, Forde, et al, 2014;Bolhuis et al, 2011;Bolhuis, Lakemond, de Wijk, Luning, & de Graaf, 2013Robinson et al, 2014;Weijzen, Smeets, & de Graaf, 2009). The underlying mechanism is considered to be less oral sensory exposure to taste when eating fast, the latter has been shown to play a major role in regulation of acute food intake (Spetter, Mars, Viergever, de Graaf, & Smeets, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…However, the results are in line with several cross-over and mostly laboratory studies have consistently shown that reducing bite sizes or eating rate within individuals decrease food intake (Andrade, Greene, & Melanson, 2008;Bolhuis, Forde, et al, 2014;Bolhuis et al, 2011;Bolhuis, Lakemond, de Wijk, Luning, & de Graaf, 2013Robinson et al, 2014;Weijzen, Smeets, & de Graaf, 2009). The underlying mechanism is considered to be less oral sensory exposure to taste when eating fast, the latter has been shown to play a major role in regulation of acute food intake (Spetter, Mars, Viergever, de Graaf, & Smeets, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…The importance of effort and mouth feel has been shown in multiple studies (30). Hunger is suppressed more or for a longer period (31,32), intake is reduced (3,12), and, through longer mastication, satiety is increased (33,34). We propose that taste and mouth feel are perhaps contributing factors to subjective feelings of fullness.…”
Section: Ad Libitum Intakementioning
confidence: 76%
“…A behavioural coding scheme was developed to record the frequencies of four 'point' events (frequency counts of bites, chews, swallows and sips) and duration of a single 'continuous' event (total oral exposure time in minutes). A number of eating parameters were derived from these coded parameters based on a previously published approach [11,12,18,43]. Total oral exposure time (minutes) was calculated as the cumulative time food spent in mouth between the bite and the swallow throughout the meal.…”
Section: Behavioural Coding Analysismentioning
confidence: 99%
“…Adults who take fewer chews before swallowing have shorter oral exposure times per bite, eat at faster rates and consume more energy [11][12][13]. By contrast, more thorough chewing of each bite increases oral exposure, reduces eating rate, reduces food intake and promotes a stronger satiety response for the same calories consumed [14][15][16].…”
Section: Introductionmentioning
confidence: 99%